Interferon-a2b and transforming growth factor-b1 treatments on HCC cell lines: are Wnt/b-catenin pathway and Smads signaling connected in hepatocellular carcinoma? - Ceballos, Maria Paula (2011)
Wnt/b-catenin pathway is often dysregulated in hepatocellular carcinoma (HCC). Activated b-catenin accumulates in the cytosol and nucleus and forms a nuclear complex with TCF/LEF factors like TCF4. Interferon-a (IFN-a) has recently been recognized to harbor therapeutic potential in prevention and treatment of HCC. Transforming Growth Factor-b1 (TGF-b1) is a mediator of apoptosis, exerting its effects via Smads proteins. One mode of interaction between Wnt/b-catenin and TGF-b1/Smads pathways is the association of Smads with b-catenin/TCF4. In this study we analyzed the effects of IFNa2b and TGF-b1 treatments on Wnt/b-catenin pathway, Smads proteins levels, b-catenin/TCF4/Smads interaction and proliferation and apoptotic death in HepG2/C3A and Huh7 cell lines. IFN-a2b and TGFb1 attenuated Wnt/b-catenin signal by decreasing b-catenin and Frizzled7 receptor proteins contents and the interaction of b-catenin with TCF4. Truncated b-catenin form present in C3A cell line also diminished after treatments. Both cytokines declined Smads proteins and their interaction with TCF4. The overall cellular response to cytokines was the decrease in proliferation and increase in apoptotic death. Treatment with Wnt3a, which elevates b-catenin protein levels, also generated the increment of Smads proteins contents when comparing with untreated cells. In conclusion, IFN-a2b and TGF-b1 proved to be effective as modulators of Wnt/b-catenin pathway in HCC cell lines holding both wild-type and truncated b-catenin. Since the inhibition ofb-catenin/TCF4/Smads complexes formation may have a critical role in slowing down oncogenesis, IFN-a2b and TGF-b1 could be useful as potential treatments in patients with HCC.